First Nations households living on-reserve experience food insecurity: prevalence and predictors among ninety-two First Nations communities across Canada - Batal, Malek (Can J Public Health, 2021)
OBJECTIVE: To describe the prevalence of food insecurity in First Nations households across Canada while identifying barriers and enablers to traditional food (TF) consumption. METHODS: The First Nations Food, Nutrition and Environment Study is a cross-Canada participatory study of on-reserve First Nations from 2008 to 2018. The Household Food Security Survey Module was used to capture income-related challenges experienced by First Nations households. Households were classified as food secure, or marginally, moderately, or severely food insecure. Barriers and enablers to TF access and use were identified describing the Indigenous experience. RESULTS: Almost half of on-reserve First Nations households were food insecure and the prevalence was higher than that for non-Indigenous households in Canada. On-reserve food insecurity prevalence was higher in western regions of Canada. First Nations households with children experienced greater food insecurity than those without children. More adults experienced severe food insecurity than children. Most adults would like to have more TF in their diet but state that factors such as financial and household constraints, industrial activities, government regulations, climate change, and fear of contamination impede greater access. Food costs were substantially higher in remote First Nations communities, but remoteness was not associated with food security in multivariable analysis. CONCLUSION: Existing systems have been unsuccessful in curbing the food insecurity in First Nations households. Improving food security hinges on achieving Indigenous Food Sovereignty, the key to long-term conservation and stewardship of the land and the co-management of these by Indigenous Peoples. Studies investigating the feasibility of increasing TF from an Indigenous perspective are required.